393. ENDOSCOPIC VACUUM THERAPY FOR PATIENTS WITH ESOPHAGEAL PERFORATION: A MULTI-CENTER RETROSPECTIVE COHORT STUDY. (24th September 2022) - Luttikhold, Joanna; Pattynama, Lisanne MD; Seewald, Stefan; Groth, Stefan; Morell, Bernhard; Ida, Satoshi; Nilsson, Magnus; Eshuis, Wietse J; Pouw, Roos E
Abstract: Esophageal perforations are associated with high morbidity. Recently, endoscopic vacuum therapy (EVT) has been introduced as a novel treatment option for esophageal perforations. This technique has so far mainly been described for anastomotic leakage after upper gastrointestinal surgery. The aim of this study was to describe the initial experiences with EVT for treatment of esophageal perforations caused by Boerhaave syndrome or with an iatrogenic cause. For this retrospective, multicenter cohort study, all patients primarily treated with EVT for an esophageal perforation at four hospitals in the Netherlands, Switzerland and Sweden between January 2018 and October 2021, were included. Data on patient characteristics, EVT and outcomes were analyzed. The primary endpoint was success rate of EVT, defined as closure of the defect, as assessed by endoscopy or CT-scan. 27 patients were included (Table 1). EVT succeeded in 24/27 patients (89%, 95%CI[71, 98]) with 16/19 using EVT alone (84%, 95%CI[60, 97]). In 8 patients an additional treatment modality was used. In 3 patients EVT failed: 2 (Boerhaave and unknown cause) deceased due to a pulmonary embolism and septic embolic stroke, and 1 (Boerhaave) underwent an additional esophagectomy. All had a 'large' perforation-size. Median hospital stay was 18 days, with median 12 days EVT-duration and 1 sponge-exchange. Additional drainage was performed in 8 patients. EVT-associated complications occurred in 3 patients: 1 iatrogenic defect-expansion from the overtube and 2 hemorrhages, which spontaneously stopped. EVT is a promising, possibly organ-preserving treatment for Boerhaave syndrome or iatrogenic esophageal perforation, with a success rate of 84–89%. More experience with the technique and indications for use will likely improve success rates in the future.